Digital technologies and "value" capture in global value chains: Empirical evidence from Indian manufacturing firms - Karishma Banga (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper examines whether digitalization can be a driver of "upgrading" in global value chains and help developing countries move into higher value-added activities. In particular, the paper provides empirical evidence on the impact of digital capabilities on product upgrading in Indian manufacturing firms participating in global value chains. Empirical analysis is undertaken on a panel of global value chain manufacturing firms in the period 2001-15, using the methodology of system generalized method-of-moments. Product upgrading is captured through a novel salesweighted average product sophistication indicator at the firm level, while principal component analysis is used to construct a digital capability index that draws information on both "hard" and "soft" digital assets of the firm. Empirical results suggest that an increase in digital capability of the firm has a significant and positive impact on its product sophistication, other things being constant. Firms with both high levels of digital capability and share of skilled labour are observed to have roughly 4-5 per cent higher product sophistication than firms with low levels of digital capability and skills. In addition, lagged product sophistication, size, industry concentration, and to some extent R&D, are also found to have a positive and significant impact on product sophistication of Indian global value chain firms. The paper further attempts to tie these empirical results to the global value chain governance literature, and advances the nexus of governance and digitalization as a key area of global value chain research.
Keywords: F1; F6; O1; O3; L1; 330; digital technologies; global value chains; upgrading; Indian manufacturing